Revenue Productivity of the Tax System in Namibia: Tax Buoyancy Estimation Approach - Shikongo, A; Shikongo, A; Kakujaha-Matundu, O; Kaulihowa, T (Journal of Economics and Behavioral Studies, 2019)
Buoyancy refers to how tax revenue responds to a gross domestic product without correcting for discretionary alterations in the tax system. The paper assessed the buoyancy of Namibia’s overall tax system in an attempt to measure the response of the tax system in entirety because of fluctuations in the national income and/or the deliberate act by the government to increase tax rate, reviewed tax code and tax machinery etc. The study employed the Engle-Granger approach to the error correction model to estimate the tax buoyancy for the period 2001 to 2014. The empirical findings from the study revealed that overall the Namibian tax system is income inelastic and not buoyant. This is confirmed by a low and negative value of 0.036 which is less than unit. Thus, the economy is not generating sufficient revenue both through discretionary tax measure and through the expansion in the economic activities. Therefore, the government need to introduce measures that will allow for more tax revenue collection to have a stable revenue base. This also means the government need to keep track of tax mobilization with growth in the gross domestic product as well as to ascertain taxes that are productive.